2010
DOI: 10.1002/9780471729259.mc10d01s18
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Maintenance of Mycobacterium abscessus

Abstract: Mycobacterium abscessus, is an emerging, rapidly growing pathogen, with the ability to cause chronic lung disease. This unit covers background information and laboratory maintenance procedures for this bacterium, including growth in liquid and on solid medium. It also contains recommendations concerning long‐term strain storage. M. abscessus is a Biosafety Level 2 organism, and the required safety measures are also discussed. Curr. Protoc. Microbiol. 18:10D.1.1‐10D.1.12. © 2010 by John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…2). As per the generation time of M. abscessus (4 to 5 h for M. abscessus [25] versus 20 to 30 min for E. coli [24]), the time points at which aliquots of the liquid cultures were plated for CFU determination were adjusted to 6, 12, and 24 h. As expected, LIN and TIG showed no bactericidal activity (Fig. 2).…”
Section: Resultsmentioning
confidence: 60%
“…2). As per the generation time of M. abscessus (4 to 5 h for M. abscessus [25] versus 20 to 30 min for E. coli [24]), the time points at which aliquots of the liquid cultures were plated for CFU determination were adjusted to 6, 12, and 24 h. As expected, LIN and TIG showed no bactericidal activity (Fig. 2).…”
Section: Resultsmentioning
confidence: 60%
“…The clinical strains grow better in Middlebrook 7H9 broth supplemented with 10% (vol/vol) oleic acid-albumin-dextrose-catalase (OADC) enrichment ( Fig. S1B), a liquid laboratory medium for culturing mycobacteria (26)(27)(28). Therefore, Middlebrook 7H9 liquid medium was primarily used in this study.…”
Section: Resultsmentioning
confidence: 99%
“…S1; Table S3). Due to concerns that the inherent instability of ␤-lactams may lead to artificially high MIC values after such prolonged incubation periods (8,(23)(24)(25)(26)(27)(28), we relied primarily on Middlebrook 7H9 liquid medium for the broth MIC assays in this study. However, we also evaluated a selection of carbapenems and cephalosporins in CAMHB and found that, in general, the MICs were indeed higher in CAMHB than Middlebrook 7H9 medium (Tables 2 and S4).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the disinfector was fully loaded might have influenced our results, but it probably mimics reality more precisely. For safety reasons, we did all mycobacterial testing in a BSL-3 Lab in a safety cabinet Class II, which meant we were limited to two steam disinfectors and disposable test tubes instead of nebulizer parts [43]. Finally, some materials are not heat-resistant enough for steam disinfection; therefore, all manufacturers of nebulizers or airway clearance devices should declare if steam disinfection is possible and choose materials suitable for steam disinfection.…”
Section: Discussionmentioning
confidence: 99%